KONDISI JAWA TENGAH PADA ABAD VIII SAMPAI ABAD XV M - Maziyah, Siti (Faculty of Humanities, Diponegoro University, 2012)
Using historical method, this research attempts to find out Central Java condition in the 8th to 15th Centuries. Collecting data from ancient inscriptions, ancient books, and earlier researches, indications are found that the 8th to 10th centuries Central Java seems existing as an old kingdom territory, but in the 11th to 15th centuries, it became a subordinate territory in the old kingdom. Data also indicate that the centre of the kingdom often changed places. Keywords: ancient Central Java, old kingdom, subordinate territory